Electronic Word-of-Mouth (E-WOM), Brand Image and Consumer Purchase Intention on Healthcare Products - Uwais Nor Rifhan Ahmad Tajuddin; Lailatul Faizah Abu Hassan; Abdul Kadir Othman; Norfadzilah Abdul Razak (Universitas Syiah Kuala, 2020)
Objective – Malaysia is ranked sixth in the Asia Pacific region for obesity and diabetes and it is ranked the first among the Southeast Asian countries. Obesity and diabetes can cause serious non-communicable diseases such as heart disease and hypertension. Buying habit and eating habit are strongly correlated and these habits are very much influenced by the e-word-of-mouth (e-WOM). However, lack of studies in this aspect creates difficulties in making a consensus on the relationships between the variables concerned. The purpose of this study was to examine the relationship between e-WOM and consumer purchase intention among Malaysian dietary supplement products’ consumers. Design/methodology – The brand image was introduced as a moderating variable between the e-WOM (quality, quantity and sender expertise) and customer purchase intention. The Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to analyse 213 usable sets of questionnaire. Results – The results indicate that e-WOM quality, e-WOM quantity and sender’s expertise have significant relationship with consumer purchase intention. However, brand image had no moderating effect in the association between e-WOM quality, e-WOM quantity as well sender’s expertise and consumer purchase intention. This study provides new insights into the e-WOM field of study, which in turn affects consumer purchase intention.